Fremskrivning af færøsk aborthistorie - Turið Nolsøe; Lena Nolsøe (Kvinder, Køn & Forskning)
The history of abortion in the Faroe Islands is an under researched aspect of both local and Nordic gender history, and analyses of how abortion has taken place are still as absent as the legal right to elective abortion in the Faroe Islands. This is not due to a lack of historical records, but to their entanglements with the gendered, class-based and national power relationships defined by the Danish kingdom’s administration of the subject.